2018
DOI: 10.3389/fpsyt.2018.00381
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum C3 and Decreased UA in Patients of Bipolar Disorder in Chinese Han Population

Abstract: The aim of this study is to explore the changes and clinical significance of serum C3, C4, hypersensitive C-reactive protein (hsCRP) and uric acid (UA) in patients of bipolar disorder (BD). In this case-control study, we recruited 141 BD patients from The Second Xiangya Hospital, Central South University, and 151 age and gender matched healthy controls (HC) from the health management central of The Second Xiangya Hospital. These patients were divided into two subgroups based on medicines use: 91 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…In contrast, no improvement was also reported by using allopurinol in treating manic symptoms (29, 30). Also, similar UA levels between manic state and remitted state were reported (20, 24).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…In contrast, no improvement was also reported by using allopurinol in treating manic symptoms (29, 30). Also, similar UA levels between manic state and remitted state were reported (20, 24).…”
Section: Introductionsupporting
confidence: 77%
“…These studies have indicated altered regulation of purinergic system in BPD (21). However, no significant differences in serum UA levels were also reported between euthymic BPD and healthy subjects (12, 20, 22, 23). Also, no significant differences were found in serum UA between the patients with manic episodes and euthymic status (20, 24, 25).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Gaya C. found that the levels of C3 in females were lower than those in males in a healthy Caucasian population (Gaya da Costa et al, 2018). In contrast, Yang X. reported that there was no significant difference in serum C3 levels between females and males in a Chinese Han population (Yang et al, 2018). Similarly, we found no obvious differences in serum C3 levels in healthy controls between genders.…”
Section: Discussionmentioning
confidence: 92%